Hydrogeological characterization to determine the deterioration of water quality in the La Yarada Media aquifer - Pino V, Edwin (2018)
The aim is to hydrogeologically characterize the La Yarada Media aquifer using the parameters by means of long-term pumping tests (Jacob and Theis recovery methods), as well as to characterize the water quality referred to the physicochemical parameters according to the current regulations and verify the possible deterioration of water quality in the aquifer. Between 2010 and 2015, 42 pumping tests were used, determining that the transmissivity to the southeast fluctuates between 602 and 4 235 m2/d (high to very high), indicating that the aquifer is free and has good hydraulic conditions, to the northwest it fluctuates between 53 and 494 m2/d, representing low and medium values, related to the tuffs of the Huaylillas Formation —being the area most affected by the continuous decrease in the piezometer level—. To the southeast, the permeability fluctuates between 13 and 86 m/d, high values unlike the sector located to the northwest where the permeability has a fluctuation between 1 and 9.8 m/d, representing low values. The overexploitation of the aquifer has caused that high and average values of transmissivity and permeability, now change to means and lows respectively in Settlement 4, since this static level was in the Quaternary deposits and has now descended, being in contact with the Huaylillas formation. Even more, it has caused the water quality to go from acceptable to bad, evidencing its deterioration that is related to the increase of the exploitation volumes and the decrease of the secondary recharge of water of good quality.